Detecting Change over Time: A Comparison of the SLUMS Examination and the MMSE in Older Adults at Risk for Cognitive Decline. (10th February 2016) - Howland, Molly; Tatsuoka, Curtis; Smyth, Kathleen A.; Sajatovic, Martha
Summary: Aims: To directly compare the 1‐year stability of Mini‐Mental State Examination (MMSE) score and Saint Louis University Mental Status (SLUMS) examination score and correlate score changes with demographic variables, clinical factors, and functional domains. Methods: A sample of 304 study participants was recruited from residential and clinical settings in Ohio. Follow‐up assessments were administered after 1 year with a retention rate of 92% (n = 281). Functional domains included the Instrumental Activities of Daily Living (IADL) scale. Results: MMSE and SLUMS scores correlated with each other ( r = 0.65, P < 0.001) and with two functional measures, including the IADL ( r = 0.27, r = 0.24, P < 0.001). However, the MMSE and SLUMS frequently placed the same subject into different categories. Rates of reversion and conversion varied between the two tests. The 1‐year changes in MMSE raw score correlated with changes in three functional domains as well as age ( P < 0.05), while SLUMS raw score changes did not correlate with any functional measures. Conclusion: Our large, longitudinal data set allowed us to compare the tests' stability, which differed between the SLUMS and MMSE. The MMSE may be more sensitive than the SLUMS to 1‐year cognitive changes influencing functional abilities.